Fatigue Test on Heavy Haul Railway Tunnel Bottom Structure With Base Cavity - Liu, Cong; Wu, Bo; Li, Rui; Wang, Feng; Tang, Qianlong (Frontiers in Earth Science, 2022)
The presence of a base cavity will degrade the bearing capacity of tunnel bottom structures, and will also have a noteworthy impact on its fatigue performance. In order to study the fatigue performance and cumulative damage to tunnel bottom structure, a series of bending fatigue tests are conducted by reference to a heavy haul railway tunnel with a base cavity. Through the tests, fatigue evolution characteristics of tunnel bottom structure with cavity are obtained, then based on the expression of S-N curves, a non-linear fatigue cumulative damage model is therefore proposed, the deflection evolution and cumulative damage evolution can be divided into three stages, and characterized with an “s-shaped” curve. The tests results reveal that the damage to the tunnel bottom structure develops rapidly when a cavity exists in the base rock, fatigue occurs more easily, and the fatigue life of specimens decreases with the increase of the stress level and cavity width.